2016
DOI: 10.1080/10717544.2016.1194498
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil shell-enriched solid lipid nanoparticles (SLN) for effective skin carcinoma treatment

Abstract: SLN possesses the capacity to be manipulated to entrap and release hydrophilic antitumor drugs with ease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 33 publications
3
26
0
Order By: Relevance
“…The method we propose is a combination of 5-FU and SLNs. There are several literature reports suggesting a great potential of such a combination [19][20][21]. Use of SLNs has a lot of advantages because, for example, they can be loaded with both hydrophobic and hydrophilic compounds, and their preparation usually does not involve any toxic solutions [22].…”
Section: Discussionmentioning
confidence: 99%
“…The method we propose is a combination of 5-FU and SLNs. There are several literature reports suggesting a great potential of such a combination [19][20][21]. Use of SLNs has a lot of advantages because, for example, they can be loaded with both hydrophobic and hydrophilic compounds, and their preparation usually does not involve any toxic solutions [22].…”
Section: Discussionmentioning
confidence: 99%
“…SLN-treated mice exhibited reduced inflammatory reactions, with reduced degrees of keratosis. 25 Studies demonstrated that FA, or vitamin B9, played a vital role in mammalian cell growth. FA has a high binding affinity with the folic acid receptor (FAR), which is upregulated on the surface of many cancer cells, and limited distribution was found in normal tissues.…”
Section: -Fu Release From Au-npsmentioning
confidence: 99%
“…Highly penetrating shell‐enriched SLNs loaded with 5‐FU were prepared using lecithin and poloxamer 188. The diffusion of 5‐FU SLN formulation was doubled when compared with the free drug …”
Section: Particulate Drug Delivery Systemsmentioning
confidence: 99%
“…Hafeez et al 24 compared dacarbazine suspension and nanoparticulate cream wherein NP cream presented higher rate of drug release and penetration in cancer cells owing to its nanostructure.Highly penetrating shell-enriched SLNs loaded with 5-FU were prepared using lecithin and poloxamer 188. The diffusion of 5-FU SLN formulation was doubled when compared with the free drug 25. Geetha et al proved the need for sesamol-loaded SLNs in skin cancer treatment since a significant flux across mouse skin upon topical application of sesamol was observed.…”
mentioning
confidence: 99%